Religious Conversion and Conflict: The Struggles of Chinese Muslim Converts in Indonesia’s Harmonious Society - Sulaiman, Rusydi; Zulkifli, Zulkifli; Ghozali, Mahbub; Gustin, Gustin (Journal of Al-Tamaddun, 2025)
The conversion of Chinese individuals to Islam reveals a range of rejections that are normalized through acceptance statements from both Chinese and Muslim communities. These acceptance statements create the impression of a harmonious interfaith relationship within a strong cultural community. This study aims to reassess the notion of harmony in the religious life of Bangka Island through the examination of various actions that fall into the category of conflict. This research employs a qualitative method utilizing a conflict formation theory analysis model, which positions the reality of conflict as a natural part of social action. The study finds that the emergence of violence accompanying the phenomenon of religious conversion through marriage, adoption, and awareness is perceived by the Chinese converts as a metric for defining conflict. The violence that is mitigated through negotiation among families and the surrounding community to foster harmony does not eliminate stigma or resolve various contradictions. Instead, it perpetuates perceptions of suspicion, discomfort, and distrust among community members, which further strains familial relationships and excludes individuals from various societal traditions. The Chinese converts become subjects of these actions, positioning them in a liminal space that limits their connections to both their Chinese families and the indigenous Muslim community. The existing relationships create an impression of seemingly harmonious interactions that could potentially erupt into new forms of violence.